Using Computer Vision and Machine Learning Algorithm to Prevent and Detect Vehicular Stalking - Fernandes, Shonal (International Journal of Computer Sciences and Engineering, 2025)
Vehicular stalking is a can be termed when a motorist is deliberately following another motorist for various reasons such as investigative, spying or stalking. Stalking has been proved to be expensive as it breaches the privacy of the victim and can be used for other illicit activities. The victim is mostly unaware that they are being stalked and it becomes difficult to report stalking to law-enforcement authorities as victims do not have strong evidence to prove. The vehicle stalking is generally in close proximity or is in the length of sight to the victim being stalked. This paper introduces an idea which can help the victim know if they are being stalked by using Computer vision and Machine learning algorithm to extract information like number plate details, vehicle type, time, colour, brand and model from the vehicles on the road during travelling to predict the stalker’s vehicle based on the occurrence and alert the victim with a report